9º Simpósio Médico Internacional de VHL; III Encontro de Famílias com a Síndrome de VHL Data: - Instituto Nacional de Câncer José de Alencar Gomes da Silva (Revista Brasileira de Cancerologia, 2010)
Resumos escolhidos para publicação. Nessa edição, os títulos foram: Extramitochondrial Fumarate Inhibits Multiple 2-OG Oxygenases in Fumarate Hydratase Deficient Cells; What is the Best Treatment for Renal Lesions in VHL?; Characterization of the VHL-ECM Pathway; Induction of Extreme Metabolic Depression by the Nucleolus; Mutation of SDHB and Inherited RCC Susceptibility; Metabolic Links to Renal Cancer; Radiosurgery for Cerebellar Hemangioblastomas; Neoplastic Diagnosis Timing Profile in von Hippel-Lindau´s Patients in a Personal Series; Regulation of the VHL Tumor Suppressor; Destructive Targeting via VHL Beyond HIF; Folliculin Functional Studies and Mouse Models of Birt-Hogg-Dube’ Syndrome; A Zebrafish Model for VHL; Relief of Intractable Nausea after Resection of Brainstem Hemangioblastoma in Patients with von Hippel-Lindau Disease: a Clinical Series; Somatic Alteration of the VHL Gene in Sporadic Renal-Cell Carcinomas as a Potential Biomarker; VHL Tumor Suppressor Protein Regulates Oncogenic Macroautophagy in Renal Clear Cell Carcinoma (RCC); Identification of Germline Mutations in the VHL Gene of Families with the von Hippel-Lindau Disease; Expression Profile in von Hippel-Lindau Disease Associated and Sporadic Clear-Cell Renal Cell Carcinomas; Proposed Changes to the VHL Handbook; Evaluation of the Somatic Alterations of the VHL Gene in Renal Cell Carcinoma Associated with von Hippel-Lindau Disease (VHL); Copy Number Variation Analysis of a Pancreatic Neuroendocrine Tumor (NET) from a Patient with von Hippel-Lindau (VHL); Molecular Dynamics Study of the Mutant pVHL Phe76del and its Interactions with Components of the pVHL Complex; Genomic Copy Number Variation Analysis in VHL-Associated Renal Cell Carcinomas Suggests Clonality; Management of Brainstem and Spinal cord Hemangioblastomas in Patients with von Hippel-Lindau Disease; The Benefits of Ultrasound in Resection of CNS Hemangioblastomas; Management of Central Nervous System Hemangioblastomas in von Hippel-Lindau Disease; Neuronal Differentiation of Stem cells by Transfer of a VHL Peptide and Regenerative Therapy; Endolymphatic Sac Tumors (ELST) in VHL Patients - Evaluation of Screening Methods in a National Study; Delineating Genotype-Phenotype Correlations Among Brazilian Families with von Hippel-Lindau Disease; Endothelial Fenestrations Associated with VHL Gene Alteration is a Potent Target of Anti-VEGF Therap; Role of Pregnancy on Hemangioblastomas in von Hippel-Lindau Disease: a Retrospective French Study; An Evaluation of the Danish National Clinical Guidelines for Von Hippel-Lindau (VHL); Vitreoretinal Surgery for Severe Retinal Capillary Hemangiomas; Oncololytic Targeting of Renal Cell Carcinoma via Encephalomyocarditis Virus; Emerging Therapeutic Options for VHL Patients: a Tale of three Studies; Altering the Stability of Mutant VHL: Potential Therapeutic Consequences; Tale of the Tail: Clinical and Functional Properties of Novel VHL Mutation (X214L) Consistent with Type 2A Phenotype and Low Risk of Renal Cell Carcinoma; Knife for Intracranial Hemangioblastomas in von Hippel-Lindau Patients. When and How?; VHL in Brazil: Genetics, Biobanking and VHL Family Care; Understanding VHL Disease: Molecular Characterization of a Spanish Series; Case Report: Radiosurgery for Endolymphatic Sac Tumor in a Patient with von Hippel-Lindau Disease; Primary Cilium: a Tumor Suppressor Organelle.